Plant clinics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Identification of the causes of ill health is the first step in crop protection. Plant protection services must also be able to anticipate pest and disease attacks and quickly identify the problem, so that the most effective treatment can be...